Genetic Variants, Circulating Level of MCP1 with Risk of Chronic Obstructive Pulmonary Disease: A Case-Control Study - Lin C; Wang Z; Shen L; Yi G; Li M; Li D (Dove Medical Press, 2021)
Chunyi Lin,1,* Zhimin Wang,2,* Lu Shen,1 Gao Yi,1 Meichan Li,1 Defu Li1 1Respiratory Medicine, The Fifth Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510700, People’s Republic of China; 2Intensive Care Unit (ICU), The Fifth Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510700, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lu ShenRespiratory Medicine, The Fifth Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510700, People’s Republic of ChinaTel/Fax +86-20-85959110Email ccc09871@21cn.comBackground: Chronic obstructive pulmonary disease (COPD) ranks one of the major causes of mortality worldwide. Inflammation is greatly involved in the pathogenesis of COPD. Monocyte chemoattractant protein-1 (MCP1) has been implicated to play an important role in the inflammatory response of various pathological processes.Methods: In this study, we conducted a hospital-based case-control study in a Chinese population, aiming to evaluate the potential associations of genetic polymorphisms of the MCP1 gene (rs1024611, rs2857656, and rs4586) and circulating level of MCP1 with COPD risk.Results: We found that rs1024611 (OR=1.37; 95% CI=1.11– 1.69; P-value=0.004) and rs4586 (OR=1.33; 95% CI=1.09– 1.63; P-value=0.006) were significantly associated with increased COPD risk. In the dominant model, both rs1024611 (OR=1.46; 95% CI=1.11– 1.92; P-value=0.006) and rs4586 (OR=1.56; 95% CI=1.18– 2.07; P-value=0.002) were significantly associated with increased COPD risk. Genotypes of rs1024611 and rs4586 with minor alleles had a significantly higher circulating level of MCP1 (P< 0.001). Meanwhile, a circulating level of MCP1 was significantly associated with increased COPD risk (OR for per quartile increment=1.35, 95% CI=1.21– 1.52, P< 0.001).Conclusion: Our study indicated that genetic polymorphisms of the MCP1 gene and circulating level of MCP1 contributed to the COPD risk in the Chinese population. MCP1 contributed importantly to the pathophysiological process and occurrence of COPD.Keywords: COPD, variation, genetic, MCP1, case-control study